2017
DOI: 10.1111/anu.12556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary lipid on growth, expression of canthaxanthin-based coloration, digestive enzymes activities and immunity in blood parrot cichlidAmphilophus citrinellus × Paraneetroplus synspilus

Abstract: A 42-day experiment was carried out to evaluate the effects of four different lipid containing diets (lipid 74.0, 105.3, 135.0, 168.1 g/kg diet) on growth, digestive enzymes activities, immunology and expression of canthaxanthin-based coloration in parrot cichlid (Amphilophus citrinellus × Paraneetroplus synspilus). Each diet contained canthaxanthin 0.05 g/kg diet. Two hundred and eighty-eight fish were randomly stocked into 12 glass aquaria to form four triplicate groups. Fish were fed one of four diets daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
4
0
1
Order By: Relevance
“…The current study discovered enhanced lipase activity in the spiral valve intestine of Acipenser Baerii when the dietary lipid level rose from L5 to L17, corresponding to growth trend. This finding was supported by the studies conducted in Manchurian trout (Chang et al, 2018), blood parrot cichlid (Amphilophus citrinellus × Paraneetroplus synspilus) (Li et al, 2018), rainbow trout (Oncorhynchus mykiss) and yellow drum (Nibea albiflora) (Wang et al, 2016). A further increase in dietary lipid led to the decrease in lipase activity from 6.42 (L17) to 5.47 (L25), indicating that the lipase secretion was inhibited by high-lipid diet.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The current study discovered enhanced lipase activity in the spiral valve intestine of Acipenser Baerii when the dietary lipid level rose from L5 to L17, corresponding to growth trend. This finding was supported by the studies conducted in Manchurian trout (Chang et al, 2018), blood parrot cichlid (Amphilophus citrinellus × Paraneetroplus synspilus) (Li et al, 2018), rainbow trout (Oncorhynchus mykiss) and yellow drum (Nibea albiflora) (Wang et al, 2016). A further increase in dietary lipid led to the decrease in lipase activity from 6.42 (L17) to 5.47 (L25), indicating that the lipase secretion was inhibited by high-lipid diet.…”
Section: Discussionmentioning
confidence: 52%
“…However, improper lipid content in the feed caused the decline in growth and health status (Meng et al, 2019;Picolo et al, 2021;Qiang et al, 2017). The lipid requirement varied from different fish species (Chang et al, 2018;Li et al, 2018;Yan et al, 2017), and the same fish had distinct lipid requirements at different development stages (Han et al, 2014;Li et al, 2016;Luo et al, 2005;Wang et al, 2016). Therefore, lipid requirement assessment is very necessary for the healthy and rapid development of the aquaculture industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding golden pompano with VO diets, the amylase, lipase and trypsin activities decreased sharply, which had a negative effect on intestinal digestion and absorption (You et al., 2019). Li, Rahman, Lin, and Chiu (2018) reported that the growth performance of blood parrot cichlid ( Amphilophus citrinellus × Paraneetroplus synspilus ) was positively correlated with intestinal digestive enzymes, which may be attributed to the regulation of the diet lipid levels. This explains why the growth performance of the LO and RO groups was better than that of the PO group.…”
Section: Discussionmentioning
confidence: 99%
“…Tabla I. Caracteres merísticos seleccionados de ejemplares de Amphilophus citrinellus colectados en la presa de Hatillo, comparados con los encontrados por Stauffer y Mckaye (2002) A. citrinellus o cíclido de Midas (conocido en el mercado de acuarios como parrot fish o cichlid midas fish), es una especie de cíclido nativa de lagos y cráteres volcánicos inundados de Nicaragua y Costa Rica (Stauffer y McKaye, 2002). Este organismo es altamente utilizado en el comercio de mascotas por sus atractivos colores (Arias, 2011) y se ha utilizado en hibridación con otras especies de acuario (Li et al, 2018;Aqmal-Naser y Ahmad, 2020).…”
unclassified